The Impact of Existentialism on Contemporary Mental Health Practices - Amani, Charlie (International Journal of Philosophy, 2024)
Purpose: The general objective of this study was to explore the impact of existentialism on contemporary mental health practices. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the impact of existentialism on contemporary mental health practices. Preliminary empirical review revealed that integrating existential principles into contemporary mental health practices significantly enhanced psychological well-being by fostering self-awareness, personal growth, and the ability to cope with existential anxieties. It demonstrated that existential therapies offered a more holistic and personalized approach to mental health care, addressing both symptomatic relief and underlying existential concerns. Additionally, the study highlighted the importance of cultural sensitivity, emphasizing that culturally adapted existential therapies were more effective and accessible across diverse cultural contexts, thereby improving mental health outcomes globally. Unique Contribution to Theory, Practice and Policy: The Existential Theory, Humanistic Theory and Cognitive Behavioural Theory may be used to anchor future studies on the impact of existentialism on contemporary mental health practices. The study recommended integrating existential principles into psychological theories, training mental health professionals in existential therapeutic approaches, and developing culturally adapted versions of these therapies. It emphasized the need for mental health policies to recognize the importance of existential concerns and support the inclusion of existential therapies in standard care. The study also suggested revising mental health education curricula to incorporate existential psychology, providing continuing education for current practitioners, and increasing public awareness to destigmatize existential issues. These steps aim to enhance theoretical frameworks, clinical practices, and policy development in mental health care.